The time course of moral perception: an ERP investigation of the moral pop-out effect. Issue 2 (4th May 2020) - Gantman, Ana; Devraj-Kizuk, Sayeed; Mende-Siedlecki, Peter; Van Bavel, Jay J; Mathewson, Kyle E
Abstract: Humans are highly attuned to perceptual cues about their values. A growing body of evidence suggests that people selectively attend to moral stimuli. However, it is unknown whether morality is prioritized early in perception or much later in cognitive processing. We use a combination of behavioral methods and electroencephalography to investigate how early in perception moral words are prioritized relative to non-moral words. The behavioral data replicate previous research indicating that people are more likely to correctly identify moral than non-moral words in a modified lexical decision task. The electroencephalography data reveal that words are distinguished from non-words as early as 200 ms after onset over frontal brain areas and moral words are distinguished from non-moral words 100 ms later over left-posterior cortex. Further analyses reveal that differences in brain activity to moral vs non-moral words cannot be explained by differences in arousal associated with the words. These results suggest that moral content might be prioritized in conscious awareness after an initial perceptual encoding but before subsequent memory processing or action preparation. This work offers a more precise theoretical framework for understanding how morality impacts vision and behavior.